Analytical results on block length optimization for decode-and-forward relaying with CSI feedback - Khormuji, M.N.; Larsson, E.G. (2007 IEEE 8th Workshop on Signal Processing Advances in Wireless Communications, 2007)
We consider block length optimization for collaborative transmit diversity using a decode-and-forward protocol assuming that the source and the relay have access to the magnitudes of all path gains. Moreover, we propose a simple scheme which requires only one bit of channel state information (CSI) feedback. We analyze the outage probabilities of all schemes for both selection combining and maximum ratio combining (MRC) at the destination. Analytical results show that even one bit of CSI feedback can provide a significant gain over conventional (non-adaptive) collaborative schemes.